Smart Plant System - Norhan, Nurulfarah Ain; Murugan , Lishaallani; Ismail , Siti Asiah; Adan, Nor Faezah (Multidisciplinary Applied Research and Innovation, 2022)
Lately, the interest in urban gardening among people increased but they do not have much time to care for their plants due to busy schedule and daily responsibilities. This project was created to provide an easier way for the owners to water their plants, which is by clicking a button in Blynk application based on the signals sent by sensors to their smartphones via Blynk. The components used to build this smart plant system is a tomato plant, temperature sensor and moisture sensor, in this case will sense the specific parameter, jumper wires, relay, solenoid water pump and NodeMCU which send the signals from sensors to Blynk application via WiFi. Some practical and theoretical studies on tomato plants’ parameters, steps to implements sensors to the system, ways to do circuit connection have been done to get more information and knowledge on this system. The project has been done and proved that this smart plant system is suitable and recommended to be used in daily life as it will ease people’s job to take good care of their plants in a smarter way even though they are busy.